Evaluasi Peraturan Daerah Kota Surabaya Nomor 7 Tahun 2002 tentang Pengelolaan Ruang Terbuka Hijau di Taman Prestasi Kota Surabaya - Rachman, Novia Ayu Dwi; Indartuti, Endang; Rukminingsih, Nunuk (Universitas 17 Agustus 1945 Surabaya, 2018)
According to the Local Regulation of the City of Surabaya No.7 of 2002 about the Management of Green Open Space relating to the management of maintaining facilities that already exist in Green Open Space (GOS), such as in Taman Prestasi. The statement of the problem of this study is